Acute ketogenic diet and ketone ester supplementation impairs race walk performance - Whitfield, J.; Burke, L. M.; McKay, A. K. A.; Heikura, I. A.; Hall, R.; Fensham, N.; Sharma, A. P. (Medicine & Science in Sports & Exercise, 2021)
Abstract The consumption of a ketogenic low-carbohydrate (CHO), high-fat (LCHF) diet increases skeletal muscle fat utilization but impairs exercise economy. Whether the concomitant increase in circulating endogenous ketone bodies (KB) alters the capacity to metabolize exogenous ketone supplements such as the popular ketone monoester is unknown. Purpose: This study aimed to determine if LCHF and ketone ester (KE) supplementation can synergistically alter exercise metabolism and improve performance. Methods: Elite race walkers (n = 18, 15 males and 3 females; V.O2peak, 62 ± 6 mL/min·kg) undertook a four-stage exercise economy test and real-life 10,000-m race before and after a 5-d isoenergetic high-CHO (HCHO, ~60%-65% fat; CHO, 20% fat; n = 9) or LCHF (75%-80% fat, <50 g·d-1 CHO, n = 9) diet. The LCHF group performed additional economy tests before and after diet after supplementation with 573 mg·kg-1 body mass KE (HVMN; HVMN Inc., San Francisco, CA), which was also consumed for race 2. Results: The oxygen cost of exercise (relative V.O2, mL/min·kg) increased across all four stages after LCHF (P < 0.005). This occurred in association with increased fat oxidation rates, with a reciprocal decrease in CHO oxidation (P < 0.001). Substrate utilization in the HCHO group remained unaltered. The consumption of KE before the LCHF diet increased circulating KB (P < 0.05), peaking at 3.2 ± 0.6 mM, but did not alter V.O2 or RER. LCHF diet elevated resting circulating KB (0.3 ± 0.1 vs 0.1 ± 0.1 mM), but concentrations after supplementation did not differ from the earlier ketone trial. Critically, race performance was impaired by ~6% (P < 0.0001) relative to baseline in the LCHF group but was unaltered in HCHO. Conclusion: Despite elevating endogenous KB production, an LCHF diet does not augment the metabolic responses to KE supplementation and negatively affects race performance.